Positive electrode material, electrochemical device, and electronic device

By preparing single-crystal positive electrode material with a sheet-like structure, controlling its thickness and aspect ratio, and adding specific elements, the problem of traditional polycrystalline materials being easily broken during the circulation process in lithium-ion batteries is solved, and the cycle life of the battery is significantly improved and safety performance.

CN119208590AActive Publication Date: 2024-12-27NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411425810.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-27
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Traditional polycrystalline ternary materials are prone to shatter during the circulation of lithium-ion batteries, resulting in an increase in side reactions of electrolytes, limiting the improvement of battery performance, especially in terms of energy density, cycle life and safety performance.

Method used

The single crystal positive electrode material with a sheet-like structure can reduce volume deformation and stress by controlling the thickness and aspect ratio, and improve the structural stability of the material and lithium ion diffusion performance by controlling the thickness and aspect ratio. The preparation method includes transition metal oxide and Sodium salt reaction and heat treatment.

Benefits of technology

It improves the cycle life, charge and discharge rate and safety performance of the electrochemical device, reduces the side reaction rate, and enhances the mechanical strength and structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208590A_ABST
    Figure CN119208590A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material, an electrochemical device and an electronic device, the positive electrode material is of a sheet structure, the chemical general formula of the positive electrode material is LixNayNiaMncO2, x is greater than or equal to 0.7 and less than or equal to 1.1, y is greater than or equal to 0.003 and less than or equal to 0.2, a is greater than or equal to 0.3 and less than or equal to 0.9, c is greater than or equal to 0.001 and less than or equal to 0.7, x + y is greater than or equal to 0.8 and less than or equal to 1.1, the thickness of the positive electrode material is 0.2-3 microns, and the length-diameter ratio of the positive electrode material is 2-10. The positive electrode material provided by the invention can enable the electrochemical device to have good dynamic performance and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to a positive electrode material, an electrochemical device and an electronic device. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, aerospace and other fields. However, higher requirements are placed on the energy density, cycle life and safety performance of lithium-ion batteries. The secondary particles of traditional polycrystalline ternary materials are easily broken during the cycle, which aggravates the side reactions of the electrolyte and limits the improvement of battery performance. Summary of the invention

[0003] The inventors of the present application have discovered that single crystal materials can not only enhance the mechanical strength of the material and reduce interface side reactions, but also improve the structural stability of the material and enhance the cycle stability.

[0004] This patent successfully prepared a single-crystal positive electrode material with a flake morphology through the regulation of preparation methods and component optimization. The flake single-crystal positive electrode material has comprehensively improved the electrochemical performance. For example, the reduction in its surface area reduces the probability of side reactions, while improving the diffusion path of lithium ions in the positive electrode material and enhancing the kinetic performance. In addition, this morphology can effectively inhibit particle pulverization, inhibit side reactions of the electrolyte, and improve the cycle life. In this technical context, the innovative process and manufacturing method for flake single-crystal ternary materials will provide important support for the development of the next generation of lithium battery technology.

[0005] In view of this, the present application provides a positive electrode material, an electrochemical device and an electronic device.

[0006] The first aspect of the present application provides a positive electrode material, the positive electrode material is a sheet structure, and the chemical formula of the positive electrode material is Li x Na y Ni a Mn c O2, 0.7≤x≤1.1, 0.003≤y≤0.2, 0.3≤a≤0.9, 0.001≤c≤0.7, 0.8≤x+y≤1.1, the thickness of the positive electrode material is 0.2μm to 3μm, and the aspect ratio of the positive electrode material is 2 to 10.

[0007] The positive electrode material of the present application is a sheet structure, which can reduce the volume deformation of the electrochemical device during the charge and discharge process, reduce the stress and cracks in the bulk phase during the cycle process, and thus improve the cycle life and safety performance of the electrochemical device compared to the spherical structure in the prior art. The present application controls the thickness range of the positive electrode material to make the volume deformation of the electrochemical device smaller, further reduce the stress and cracks in the bulk phase during the cycle process, and improve the cycle life. The present application also provides a shorter transmission path for lithium ions by controlling the aspect ratio, thereby increasing the migration speed of lithium ions in the positive electrode material, thereby increasing the charge and discharge rate of the electrochemical device.

[0008] Based on the first aspect, in some possible embodiments, 0.8≤x≤1.01, 0.01≤y≤0.08, 0.3≤a≤0.9, 0.1≤c≤0.7, 0.82≤x+y≤1.02, the thickness of the positive electrode material is 0.4μm to 2.3μm, and the aspect ratio of the positive electrode material is 3.9 to 7.5.

[0009] Based on the first aspect, in some possible implementations, the thickness of the positive electrode material is 1 μm to 3 μm; and the aspect ratio of the positive electrode material is 3.5 to 8.

[0010] The present application further improves the cycle life, charge and discharge rate, and safety performance of the electrochemical device by further regulating the thickness and aspect ratio of the oxide positive electrode material to meet the above range.

[0011] Based on the first aspect, in some possible implementations, the thickness of the positive electrode material is 1.4 μm to 2 μm; and the aspect ratio of the positive electrode material is 4.5 to 5.5.

[0012] The present application further improves the cycle life, charge and discharge rate, and safety performance of the electrochemical device by further regulating the thickness and aspect ratio of the oxide positive electrode material to meet the above range.

[0013] Based on the first aspect, in some possible implementations, the positive electrode material includes element Q, the element Q includes F, and also includes at least one of B, Si and P.

[0014] In the present application, by adding the above-mentioned element Q, due to the difference between the electronic structure of the element Q and the electronic structure of the transition metal elements Ni and Mn, the interaction between the element Q and the oxygen element and between the oxygen element and Ni and Mn will be improved, the phase change during the cycle process will be reduced, and the cycle performance of the electrochemical device will be further improved. In addition, after the element Q is added, the lithium position and / or the transition metal position is replaced, the structural stability of the material is improved, and the diffusion coefficient of lithium ions is increased, thereby improving the kinetic performance and cycle stability of the electrochemical device.

[0015] Based on the first aspect, in some possible implementations, the average thickness of the positive electrode material is 1 μm to 2.5 μm.

[0016] When the average thickness of the positive electrode material of the present application meets the above range, the volume deformation of the electrochemical device is smaller, further reducing the stress and cracks in the bulk phase during the cycle process, thereby improving the cycle life.

[0017] Based on the first aspect, in some possible embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 5m 2 / g.

[0018] The present application controls the specific surface area of ​​the positive electrode material to meet the above range, reduces the contact area between the positive electrode material and the electrolyte, reduces the side reaction of the electrolyte on the surface of the positive electrode material during the charge and discharge process of the electrochemical device, improves gas production, and further improves the cycle life of the electrochemical device.

[0019] The second aspect of the present application provides a method for preparing a positive electrode material, comprising: reacting a transition metal oxide and / or a transition metal hydroxide with a sodium salt to obtain a sodium-containing intermediate, wherein the reaction temperature is 950°C to 1050°C and the reaction time is 12h to 48h; adding the intermediate to an organic solvent or molten salt containing a lithium element and heating it, the heating temperature is 240°C to 600°C, the heating time is 2h to 24h, stirring, washing, centrifuging and drying to prepare a positive electrode material.

[0020] In the above preparation method, by controlling the temperature and time of the reaction between the transition metal oxide and / or transition metal hydroxide and the sodium salt, the atomic ratio of each transition metal element (Ni, Mn) and element Q in the positive electrode material is controlled, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0021] The third aspect of the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the above-mentioned positive electrode material, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0022] Based on the third aspect, in some possible embodiments, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes a silicon-based negative electrode material and / or graphite, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0023] Based on the third aspect, in some possible implementations, the electrolyte includes adiponitrile and fluoroethylene carbonate, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0024] A fourth aspect of the present application provides an electronic device, comprising the above-mentioned electrochemical device, which has good cycle life, charge and discharge rate and safety performance, which is beneficial to improving the service life and safety of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the surface of the positive electrode material of Example 3. DETAILED DESCRIPTION

[0026] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.

[0027] Cathode Materials An embodiment of the present application provides a positive electrode material, the positive electrode material is a sheet structure, and the chemical formula of the positive electrode material is Li x Na y Ni a Mn c O2, 0.7≤x≤1.1, 0.003≤y≤0.2, 0.3≤a≤0.9, 0.001≤c≤0.7, 0.8≤x+y≤1.1, the thickness of the positive electrode material is 0.2μm to 3μm, for example, the thickness can be 0.2μm, 0.5μm, 0.7μm, 0.9μm, 1.1μm, 1.3μm, 1.5μm, 1.7μm, 1.9μm, 2.1μm, 2.3μm, 2.5μm, 2.7μm, 2.9μm, 3μm or any value within the range composed of any of the above numerical values; the aspect ratio of the positive electrode material is 2 to 10, for example, the aspect ratio can be 2, 2.5, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10.

[0028] The positive electrode material of the present application is a sheet structure, which can reduce the volume deformation of the electrochemical device during the charge and discharge process, reduce the stress and cracks in the bulk phase during the cycle process, and thus improve the cycle life and safety performance of the electrochemical device compared to the spherical structure in the prior art. The present application controls the thickness range of the positive electrode material to make the volume deformation of the electrochemical device smaller, further reduce the stress and cracks in the bulk phase during the cycle process, and improve the cycle life. The present application also provides a shorter transmission path for lithium ions by controlling the aspect ratio, thereby increasing the migration speed of lithium ions in the positive electrode material, thereby increasing the charge and discharge rate of the electrochemical device.

[0029] The present application further regulates 0.8≤x≤1.01, 0.01≤y≤0.08, 0.3≤a≤0.9, 0.1≤c≤0.7, 0.82≤x+y≤1.02, the thickness of the positive electrode material is 0.4μm to 2.3μm, and the aspect ratio of the positive electrode material is 3.9 to 7.5, thereby further improving the cycle life, charge and discharge rate and safety performance of the electrochemical device.

[0030] The present application further improves the cycle life, charge and discharge rate, and safety performance of the electrochemical device by further adjusting the thickness of the oxide positive electrode material to 1 μm to 3 μm and the aspect ratio of the positive electrode material to 3.5 to 8.

[0031] The present application further improves the cycle life, charge and discharge rate, and safety performance of the electrochemical device by further adjusting the thickness of the oxide positive electrode material to 1.4 μm to 2 μm and the aspect ratio of the positive electrode material to 4.5 to 5.5.

[0032] In some embodiments, the positive electrode material includes element Q, element Q includes F, and also includes at least one of B, Si and P.

[0033] In the present application, by adding the above-mentioned element Q, due to the difference between the electronic structure of the element Q and the electronic structure of the transition metal elements Ni and Mn, the interaction between the element Q and the oxygen element and between the oxygen element and Ni and Mn will be improved, the phase change during the cycle process will be reduced, and the cycle performance of the electrochemical device will be further improved. In addition, after the element Q is added, the lithium position and / or the transition metal position are replaced, the structural stability of the positive electrode material is improved, and the diffusion coefficient of lithium ions is increased, thereby improving the kinetic performance and cycle stability of the electrochemical device.

[0034] In some embodiments, the average thickness of the positive electrode material is 1 μm to 2.5 μm. For example, the average thickness can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm or any value within the range composed of any of the above values.

[0035] When the average thickness of the positive electrode material of the present application meets the above range, the volume deformation of the electrochemical device is smaller, further reducing the stress and cracks in the bulk phase during the cycle process, thereby improving the cycle life.

[0036] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 5 m 2 / g, for example, the specific surface area can be 0.5 m 2 / g, 0.7 m2 / g, 0.9m 2 / g, 1.2 m 2 / g, 1.5 m 2 / g, 1.8 m 2 / g, 2 m 2 / g, 2.3 m 2 / g, 2.6 m 2 / g, 2.9 m 2 / g, 3 m 2 / g, 3.2 m 2 / g, 3.5 m 2 / g, 3.7 m 2 / g, 4 m 2 / g, 4.2 m 2 / g, 4.5 m 2 / g, 4.7 m 2 / g, 5m 2 / g or any value within the range consisting of any of the above values.

[0037] The present application controls the specific surface area of ​​the positive electrode material to meet the above range, reduces the contact area between the positive electrode material and the electrolyte, reduces the side reaction of the electrolyte on the surface of the positive electrode material during the charge and discharge process of the electrochemical device, improves gas production, and further improves the cycle life of the electrochemical device.

[0038] The present application also provides a method for preparing a positive electrode material, comprising: reacting a transition metal oxide and / or a transition metal hydroxide with a sodium salt to obtain a sodium-containing intermediate, wherein the reaction temperature is 950°C to 1050°C, and the reaction time is 12h to 48h; adding the intermediate to an organic solvent or molten salt containing a lithium element for heating, stirring, washing, centrifuging, and drying to prepare a positive electrode material, wherein the heating temperature is 240°C to 600°C, and the heating time is 2h to 24h.

[0039] The sodium salt includes at least one of sodium carbonate, sodium oxalate, sodium acetate, sodium nitrite, sodium nitrate, sodium hydroxide and sodium citrate.

[0040] The intermediate is added into an organic solvent or molten salt containing lithium element and heated by at least one of resistance wire heating, microwave heating and plasma sintering.

[0041] In the above preparation method, transition metal oxides and transition metal hydroxides provide the source of transition metal elements (Ni, Mn) and element Q in the positive electrode material. By controlling the temperature and time of the reaction between the transition metal oxide and / or transition metal hydroxide and the sodium salt, the atomic proportion of each transition metal element (Ni, Mn) and element Q in the positive electrode material can be controlled, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0042] Positive electrode The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, for example, including but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active material layer includes the positive electrode material of the present application, so that the electrochemical device has good cycle life, charge and discharge rate, and safety performance.

[0043] The positive electrode active material layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. At least one.

[0044] The positive electrode active material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0045] Negative electrode The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode active material, and optionally a conductive agent, a binder and a thickener.

[0046] The negative electrode active material of the present application includes silicon-based negative electrode material and / or graphite, and the silicon-based negative electrode material specifically includes silicon-carbon composite material. The positive electrode material of the present application is matched with silicon-based negative electrode material or graphite, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0047] The specific type of the conductive agent is not subject to specific restrictions and can be selected according to needs. As an example, the conductive agent includes but is not limited to conductive graphite, superconducting carbon, at least one of acetylene black, conductive carbon black (Super P), Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0048] The specific type of the binder is not subject to specific restrictions and can be selected according to needs. As an example, the binder includes but is not limited to at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin and carboxymethyl cellulose.

[0049] The specific type of thickener is not subject to specific limitation and can be selected according to the requirements. As an example, the thickener includes but is not limited to sodium carboxymethyl cellulose (CMC).

[0050] However, the present application is not limited to the above materials, and the negative electrode plate of the present application may also use other known materials that can be used as negative electrode active materials, conductive agents, binders and thickeners.

[0051] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0052] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0053] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).

[0054] Electrolyte According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.

[0055] In some embodiments, the additives include adiponitrile and fluoroethylene carbonate. The additives of the present application are selected from adiponitrile and fluoroethylene carbonate, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0056] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(difluorooxalatoborate) LiBF2(C2O4) (LiDFOB).

[0057] In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate.

[0058] Electrochemical Devices The electrochemical device of the present application also includes a housing (such as a packaging bag) for accommodating the above-mentioned positive electrode sheet, separator, negative electrode sheet and electrolyte, as well as other components known in the electrochemical field, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the housing, which can be a housing known in the art, as long as the purpose of the present application can be achieved. For example, an aluminum-plastic film packaging bag can be used. The present application has no special restrictions on the type of chemical device, which can include any device that undergoes an electrochemical reaction. The electrochemical device containing the above-mentioned positive electrode material has good cycle life, charge and discharge rate and safety performance.

[0059] Electronic Devices The electrochemical device is applied to an electronic device to supply power to a load in the electronic device. Moreover, the electrochemical device has good cycle life, charge and discharge rate and safety performance, which is beneficial to improving the service life and safety of the electronic device. Among them, the electronic device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0060] Example 1 <Preparation of positive electrode material> 1. In a 5L continuous reactor, nickel sulfate and manganese sulfate were mixed in an aqueous solution at a molar ratio of Ni:Mn=50:50 to prepare a 2M metal salt solution, and the solution was connected to the reactor. 3L of deionized water was added to the reactor and nitrogen was introduced at a rate of 2L / min to remove dissolved oxygen. Then, a certain amount of 3M NaOH solution was introduced into the reactor, and the mixture was stirred evenly at 1200rpm at 60°C and the pH was adjusted to 12.0. Then, 2M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution were gradually added at a certain rate, and the reaction was fully reacted for 24h to obtain Ni 0.5 Mn 0.5 (OH)2 precursor.

[0061] 2. Prepare Ni 0.5 Mn 0.5The (OH)2 precursor and sodium carbonate were fully mixed at a molar ratio of (Ni+Mn):Na = 1:1.05, heated to 1000°C at a heating rate of 5°C / min, reacted for 24h, cooled to 70°C at a cooling rate of 25°C / min, and finally crushed and sieved to obtain a sodium-containing intermediate.

[0062] 3. Mix the sodium-containing intermediate with a lithium salt (a mixture of lithium hydroxide and lithium nitrate in a molar ratio of 1:1) in a mass ratio of 1:10, heat to 600°C at a heating rate of 10°C / min, and heat for 24 hours. Then cool to room temperature at a cooling rate of 50°C / min in a mixture of Ar and air (volume ratio of 1:1), fully soak and stir in deionized water, and obtain the positive electrode material through suction filtration, vacuum drying, crushing, and sieving.

[0063] 4. The above-mentioned positive electrode material and NaF powder were fully mixed, heated to 650°C in a mixture of Ar and air (volume ratio of 1:1) at a heating rate of 10°C / min for 12 hours, cooled to room temperature at a cooling rate of 10°C / min, crushed and sieved to obtain the positive electrode material of the present application.

[0064] <Preparation of positive electrode sheet> The binder polyvinylidene fluoride (PVDF), the conductive agent conductive carbon black (Super P), and the positive electrode material are mixed uniformly in a weight ratio of 1.5:1.5:97, and N-methylpyrrolidone (NMP) is added as a solvent to obtain a positive electrode slurry, wherein the viscosity of the positive electrode slurry is 3000 mPas to 6000 mPas; the positive electrode slurry is uniformly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 120°C for 1 hour to obtain a positive electrode sheet coated with a positive electrode material layer with a thickness of 60 μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 120°C for 1 hour, and then cold press, cut pieces, and weld the pole ears to obtain a positive electrode sheet with a specification of 74mm×867mm.

[0065] <Preparation of negative electrode sheet> After mixing the negative electrode active material graphite, the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber in a weight ratio of 96:2:2, deionized water was added, and the mixture was stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%; the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 100°C to obtain a negative electrode sheet with a coating thickness of 80μm and a single-sided negative electrode material layer. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer. Dry under vacuum conditions at 100°C for 1 hour, and then obtain a negative electrode sheet with a specification of 78mm×875mm after cold pressing, cutting, and slitting.

[0066] <Preparation of Electrolyte> In an argon atmosphere glove box with a water content of <10ppm, propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1, and then the fully dried lithium salt LiPF6 was dissolved in the above non-aqueous solvent, and 2% 1,3-propane sultone was added to prepare the electrolyte in the embodiment. Based on the mass of the electrolyte, the mass proportion of LiPF6 is 13%. <Preparation of isolation membrane> A polypropylene / polyethylene composite film with a thickness of 7 μm was used as the isolation membrane.

[0067] <Preparation of lithium-ion soft-pack batteries> The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming (forming upper limit voltage is 4.35V, forming temperature is 85℃, and forming standing time is 2 hours), degassing, trimming and other processes, a lithium-ion soft-pack battery is obtained.

[0068] Example 2 to Example 10 The difference between Examples 2 to 10 and Example 1 is that in <Preparation of Positive Electrode Materials>, the ratio of precursors Ni and Mn, reaction temperature, reaction time, heating temperature and heating time are different, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0069] Embodiment 11 The difference between Example 11 and Example 1 is that in <Preparation of Electrolyte>, 1% of fluorocarbonate and 0.5% of adiponitrile are further added, and the remaining conditions / preparation method are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0070] Example 12 The difference between Example 12 and Example 1 is that in step 4 of <Preparation of Positive Electrode Material>, in addition to adding NaF, boric acid is also added, and the remaining conditions / preparation methods are the same as those of Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0071] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step 1 of <Preparation of Positive Electrode Material>, the molar ratio of Ni and Mn is adjusted to 20:80; in step 4 of <Preparation of Positive Electrode Material>, NaF is not added, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Tables 1 and 2.

[0072] Test Method (1) Test method for length, width and thickness of positive electrode materials A scanning electron microscope (instrument model: Thermo Scientific FEI-Apreo S SEM, acceleration voltage: 0.2KV to 30KV) was used to observe the morphology of the positive electrode material particles and take microscopic photos. 30 flaky particles were randomly selected from the photos, and the average value of the longest length of the flaky particle plane was measured using the measuring tool provided by the scanning electron microscope as the length, the average value of the maximum width perpendicular to the maximum length as the width, and the average thickness perpendicular to the flaky plane as the thickness, where the aspect ratio is the ratio of length to width.

[0073] (2) Battery cell specific capacity test The lithium-ion soft-pack battery was charged to 4.35V at 0.04C at 25°C, then charged to 0.02C at 4.35V; left to stand for 5 minutes, then discharged to 2.8V at 0.04C, and left to stand for 5 minutes. The discharge capacity divided by the total mass of the positive electrode active material is the specific capacity of the battery cell.

[0074] (3) 85℃ storage thickness expansion test The lithium-ion soft-pack battery was charged to 4.35V at a constant current of 0.5C at 25°C, and then charged to 0.05C at a constant voltage of 4.35V. The thickness of the lithium-ion soft-pack battery was measured and recorded with a micrometer as H0. The lithium-ion soft-pack battery was then placed in an 85°C oven for 24 hours. The lithium-ion soft-pack battery was taken out and measured and recorded with a micrometer as H1. The thickness expansion rate of the lithium-ion soft-pack battery after storage at 85°C for 24 hours (%) = (H1-H0) / H0×100%.

[0075] (4) 45℃ cycle capacity retention test Place the lithium-ion soft-pack battery in a 45℃ constant temperature box and let it stand for 30 minutes to make the lithium-ion soft-pack battery reach a constant temperature; charge the lithium-ion soft-pack battery that has reached a constant temperature to 4.35V at 1.5C constant current at 45℃, and then charge it to 0.02C at 4.35V; let it stand for 5 minutes, and then discharge it to 2.8V at 4C constant current, let it stand for 5 minutes, and test the discharge capacity of this time as the first cycle discharge capacity; charge and discharge the battery 500 times in this way, and the discharge capacity of the 500th cycle is recorded as the 500th cycle discharge capacity. The capacity retention rate (%) of the lithium-ion soft-pack battery cycled 500 times at 45℃ = 500th cycle discharge capacity / first cycle discharge capacity × 100%.

[0076] (5) 2C / 0.1C test method The lithium-ion soft-pack battery is charged to 4.35V at 0.7C at 25°C, and then charged to 0.025C at 4.35V; let it stand for 5 minutes, and then discharged to 2.8V at 0.1C; let it stand for 5 minutes. Charge to 4.35V at 0.7C, and then charge to 0.025C at 4.35V; let it stand for 5 minutes, and then discharge to 2.8V at 2C; let it stand for 5 minutes. The ratio of the above 2C constant current discharge capacity divided by the 0.1C constant current discharge capacity is the rate 2C / 0.1C.

[0077] (6) Specific surface area test method In accordance with the national standard "Determination of the specific surface area of ​​solid substances by gas adsorption BET method" (GB / T 19587-2017), the specific surface area of ​​the positive electrode material was tested by nitrogen adsorption method using a specific surface area analyzer (model TristarⅡ3020).

[0078] (7) Element content test Use aqua regia solution to dissolve the positive electrode material (for example, 0.4 g of positive electrode material uses 10 ml of aqua regia solution (aqua regia solution is a 1:1 volume ratio of aqua regia to deionized water, and aqua regia is a 3:1 volume ratio of concentrated hydrochloric acid to concentrated nitric acid), dilute to 100 mL, and then use an ICP analyzer to test the mass percentage of elements such as Li, Na, Ni and manganese in the solution.

[0079] Figure 1 This is a SEM image of the surface of the positive electrode material of Example 3. Figure 1 It can be seen that the positive electrode material of the present application is a sheet-like single crystal morphology, which is beneficial to shorten the transmission path of lithium ions, thereby improving the kinetic performance of the electrochemical device.

[0080] Among them, the parameters of Examples 1 to 12 and Comparative Example 1 are recorded in Tables 1 and 2.

[0081] Table 1 Table 2 Note: “ / ” in Table 2 means there is no corresponding substance or parameter.

[0082] It can be seen from Table 1 and Table 2 that compared with Example 1, Examples 2 to 10, by adjusting the reaction temperature, reaction time, heating temperature and heating time in <Preparation of Positive Electrode Material>, will affect the cycle, rate and safety performance of the electrochemical device.

[0083] Compared with Example 1, Example 11 further improves the high temperature (45°C and above) cycle performance, charge and discharge rate, and safety performance of the electrochemical device by adding 5% of fluorocarbonate and 0.5% of adiponitrile in <Preparation of electrolyte>.

[0084] Compared with Example 1, Example 12 further improves the high temperature (45° C. and above) cycle performance and safety performance of the electrochemical device by adding boric acid in step 4 of <Preparation of positive electrode material>.

[0085] In step 1 of <Preparation of Positive Electrode Material> of Comparative Example 1, the molar ratio of Ni and Mn is adjusted to 20:80, and NaF is not added in step 4. It can be seen that compared with Comparative Example 1, Example 1 significantly improves the high temperature (45°C and above) cycle performance and safety performance of the electrochemical device.

[0086] In addition, the present application controls the thickness of the positive electrode material to be within the range of 0.2 μm to 3 μm, and controls the aspect ratio of the positive electrode material to be within the range of 2 to 10, so that the electrochemical device has good cycle life, charge and discharge rate and safety performance.

[0087] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a sheet structure, and the chemical formula of the positive electrode material is Li x Na y Ni a Mn c O2, 0.7≤x≤1.1, 0.003≤y≤0.2, 0.3≤a≤0.9, 0.001≤c≤0.7, 0.8≤x+y≤1.1, the thickness of the positive electrode material is 0.2μm to 3μm, and the aspect ratio of the positive electrode material is 2 to 10.

2. The positive electrode material according to claim 1, characterized in that 0.8≤x≤1.01, 0.01≤y≤0.08, 0.3≤a≤0.9, 0.1≤c≤0.7, 0.82≤x+y≤1.02, the thickness of the positive electrode material is 0.4μm to 2.3μm, and the aspect ratio of the positive electrode material is 3.9 to 7.

5.

3. The positive electrode material according to claim 1, characterized in that The thickness of the positive electrode material is 1 μm to 3 μm; the aspect ratio of the positive electrode material is 3.5 to 8.

4. The positive electrode material according to claim 1, characterized in that The thickness of the positive electrode material is 1.4 μm to 2 μm; the aspect ratio of the positive electrode material is 4.5 to 5.

5.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The positive electrode material includes element Q, and the element Q includes F and at least one of B, Si and P.

6. The positive electrode material according to any one of claims 1 to 4, characterized in that: The average thickness of the positive electrode material is 1 μm to 2.5 μm.

7. The positive electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area of ​​the positive electrode material is 0.5 m 2 / g to 5 m 2 / g.

8. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises the positive electrode material as claimed in any one of claims 1 to 7.

9. The electrochemical device according to claim 8, characterized in that The negative electrode plate includes a negative electrode active material, and the negative electrode active material includes a silicon-based negative electrode material and / or graphite.

10. The electrochemical device according to claim 8, characterized in that The electrolyte includes adiponitrile and fluoroethylene carbonate.

11. An electronic device, characterized in that: Comprising the electrochemical device according to any one of claims 8 to 10.

Citation Information

Patent Citations

  • Positive electrode material and electrochemical device comprising same

    CN114762151A

  • Positive electrode material, electrochemical apparatus, and electronic device

    US20240266531A1

  • Positive electrode active material for secondary batteries, and secondary battery

    WO2024162139A1

  • Positive electrode plate, electrochemical apparatus, and electric apparatus

    WO2024197576A1